Kajian Parameter Optimal Desain Turbin Vortex Pada Head Sangat Rendah - Suarda, Made; Sucipta, Made; Wahyuni, Ni Putu Rika Anindya; Dewi, Ni Ketut Restia (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2023)
The gravity water flow vortex turbine is a new type of turbine system for very low heads such as irrigation flows. The prototype was first installed on the Obergrafendorf river - Austria in 2006. This type of turbine consists of a channel to direct the water flow and a basin which functions to form a vortex flow where the rotating energy of the water rotates the turbine runner. Because this system is a new technology and there is limited literature available, starting that year many researchers around the world began to investigate and develop this system as an environmentally friendly renewable energy source. So, this turbine system requires further research to optimize its installation. Therefore, in this research, a literature review was carried out regarding the design parameters resulting from the development of the system. The optimum design parameters that have been achieved include: a rectangular flow channel with a notch angle of 27°-30°, a cone-shaped basin with an angle of 65° where the ratio of outlet to inlet diameter is 14%-18% and the ratio of height to inlet diameter is 1.5, while the ratio of the runner height to the basin height is 31% -32%, installed at a position 60% from the top end of the basin, and the runner blades are curved with an angle of 50°-60° and the cut ratio is no more than 15% with a number of blades of 5 blades. Next, a test model of the vortex turbine system was created and tested at a maximum water flow rate of 8.4 l/s and a maximum head of 0.755 meters. The maximum performance produced that: 30-watt output power, 180 rpm rotation, and 49% efficiency. This performance can be further improved by optimizing the runner blade design.